It’s All Greek to Me! Using Authentic Readings to Improve Knowledge of the English Language and Western Culture - Davenport, Charity (Open textbook library., 2019)
“It’s All Greek to Me!” has everything—entertaining stories, academic articles in a variety of disciplines, vocabulary crossover in literary and academic readings, connections to local, American, and Western culture, and plenty of chances for critical thinking for advanced students of English as a Second Language (ESL). All readings are authentic with minimal adaptation from a variety of sources. This textbook also gives help for advanced level grammar and writing issues, using outside sources, and reading and vocabulary strategies.